USE OF WIDAL TEST IN DIAGNOSIS OF TYPHOID FEVER IN NORTH INDIAN POPULATION BY ESTIMATING BASELINE TITER IN CONTROL GROUP - Jeevan, Shetty (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was undertaken to establish a cutoff significant titer for Widal test using healthy volunteers as control group. Utilizing the baseline titer obtained from the control group, a diagnosis of typhoid fever was made in the test group comprising outpatients and inpatients. Methods: Blood samples were collected from healthy volunteers and patients attending G.S Medical College and Hospital, Pilkhuwa, over a period of 6 months from September 2016 to March 2017. Antibodies to Salmonella typhi (TO, TH) and Paratyphi A (AH) and Paratyphi B (BH) are determined by this tube agglutination test. A total of 124 healthy controls and 303 patients having clinical suspicion of typhoid fever were subjected to Widal test. Results: In healthy control group, titer TO ≥20 was observed in 43 (34.7%), TO ≥40 in 48 (38.7%), TO≥80 in 25 (20.2%), and titer TO ≥160, TO ≥320 was observed in none of the control group. Titer TH ≥40 in 58 (46.8%), AH ≥40 in 7 (5.6%), and BH ≥40 in 13 (10.5%) were observed in the control group. Among the test group, 96 (31.7%) sera were positive out of 303 clinically suspected enteric fever by the Widal test. Among different age group studied, 34 (46.6%) patients belonged to the age group of 11-20 years which formed the highest followed by the age group of 21-30 years (33.3%). Conclusion: Based on the study, a cutoff titer of ≥160 for anti-O and anti-H antibodies and titer of ≥80 for anti-AH and anti-BH antibodies be considered as significant titer in diagnosis of enteric fever in this region. The baseline titer helps in early recognition and treatment of this serious health problem.